RECORDS FOLCLORISTICHNI OF STEPAN PUSHIK: «PROVERBS» FOR YOU, ADULTS AND CHILDREN» - Didic, O. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
Review of book of S.G. Pushik «Proverbs: heard, wrote down and put in order Stepan Pushyk» . – Ivano-Frankivs’k: «Folio», 2009. – 360 s.